Propuesta de un plan estratégico para el restaurant Manila de la ciudad de Loja en el periodo 2015-2019 - Celi Celi, Sandra Yanela (2015)
Strategic Planning aims bathroom profound changes Organizations, and lets you concentrate on the strengths of the organization, help to address the problems of changes in the external environment. At present most of the organizations recognize the importance of the paragraph Do Growth strategic planning and long-term welfare. The present study aims to contribute to the Organizational Development Restaurant Manila, which is allow a long-term UN better service and performance. Development Project information collection was performed by applying an interview to the Manager; 8 Personal al Polls working in the company and 395 Polls one Clients in order to obtain information to Perform UN Situational diagnosis Restaurant Manila, The I allowed • analyze the external and internal service business aspects at the same time Knowing the true and real state of As we find the same. With this background, if I make a SWOT matrix in the restaurant S. Manila para determine external factors (opportunities and threats) and internal factors (strengths and weaknesses); with their respective parent As stories: SWOT, same leading to the development of four types of strategies FA, FO, DA; DO; While for MEFI matrix, we have taken as Percent Maximum 100%, the same that will be distributed according to the impact to represent each factor and an SU This Time It will be one every Divided para Their items. : Besides the total weight it is 1.00 and the weighted weight is 2.84; While para Matrix As if I MEFE Maximum Percentage 100%, giving total of 1.00 and 2.82 weight is weighted; WHILE MPC that the weight matrix is 1.00 and the weights are: 3.45; 3.90 and 1.55. 4 strategic objectives and to improve the service provided by the Restaurant Manila to the general public, as well as communication between different areas was also performed. 1. Improve the structures and know the hierarchical levels of the organization through appropriate organizational design for the company. 2. Improve communication and coordination of an organization with administrative manuals. 3. Improve customer service. 4. To publicize the services provided by the Restaurant Manila. In turn, the mission and vision defined Restaurant Manila, the same as set meeting all its goals. The total cost of the objectives of the proposal are: $ US $ 5,186. Subsequently the findings and recommendations where allowed to know the reality of how is the Restaurant in relation to strategic planning, the same that will be brought to the attention of the manager was raised Restaurant Manila